Has the Dutch Miracle Come to an End? - Jan C. van Ours (Center for Economic Studies and ifo Institute (CESifo), 2003)
In the past decades unemployment in the Netherlands has gone down substantially. The main suspects responsible for this decline are the growth of part-time labor, the reform of the benefit system and wage moderation. Nevertheless, in 2002 the unemployment rate in the Netherlands has increased somewhat. However, since the huge decline in unemployment was due to structural improvements in the functioning of the labor market there is not a lot of reason to worry about the recent rise in unemployment. The current structure of the labor market is a lot healthier' than it was in the early 1980s. Therefore, the upward movement of the unemployment rate is bound to be a mild one.
Keywords: 330; unemployment; employment.